2014
DOI: 10.1007/s11605-014-2596-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bile Duct Transcription Factor HNF1β Predicts Early Tumor Recurrence and Is a Stage-Independent Prognostic Factor in Hepatocellular Carcinoma

Abstract: Our results indicated that HNF1β expression is a crucial predictor of poor prognosis in HCC and is independent of tumor stage. Moreover, concomitant HNF1β and CK19 expressions exhibited additive adverse effects in HCC, confirming that HCC with biliary differentiation has a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
1
9
1
Order By: Relevance
“…The CA-IX protein was detected in the formalin-fixed, paraffin-embedded sections of HCC and liver tissue using a labeled streptavidin-biotin method after antigen retrieval, as previous studies [ 29 ]. The tissue sections were dewaxed and rehydrated.…”
Section: Methodsmentioning
confidence: 99%
“…The CA-IX protein was detected in the formalin-fixed, paraffin-embedded sections of HCC and liver tissue using a labeled streptavidin-biotin method after antigen retrieval, as previous studies [ 29 ]. The tissue sections were dewaxed and rehydrated.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, research on HNF-1β has mainly focused on a variety of diseases caused by HNF-1β mutations during organ development, such as maturity-onset diabetes of the young type 5 (MODY5), renal cysts, neonatal diabetes, pancreatic hypoplasia, abnormal liver function, cholestasis, etc. 14, 15 . HNF-1β down-regulation probably promotes fetal liver stem/progenitor cells differentiation into hepatocytes 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Because H3K36me3 was detected in the biliary epithelium but hepatocytes were not detected in nontumorous liver parenchyma, and because our published studies indicated that HCC with biliary differentiation is associated with poor prognosis [ 18 , 19 ], we were interested in the association of H3K36me3 positivity with biliary markers. We found a strong association between H3K36me3 positivity and biliary marker expression.…”
Section: Discussionmentioning
confidence: 99%
“…Archival formalin-fixed, paraffin-embedded sections of nontumorous liver tissue and HCC specimens were used to analyze the expression of H3K36me3, CK19, and HNF1β using the streptavidin-biotin immunoperoxidase technique, as described previously [ 19 , 21 ]. The primary antibodies used were a rabbit polyclonal antibody against human H3K36me3 (1:100 dilution, Abcam, Cambridge, MA, USA), a mouse monoclonal antibody against human CK19 (1:200 dilution, Leica Biosystems, Newcastle, UK), and a rabbit polyclonal antibody against human HNF1β (1:100 dilution; Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation